2019
DOI: 10.3389/fmicb.2019.00367
|View full text |Cite
|
Sign up to set email alerts
|

IncX4 Plasmid Carrying the New mcr-1.9 Gene Variant in a CTX-M-8-Producing Escherichia coli Isolate Recovered From Swine

Abstract: We studied a commensal colistin-resistant Escherichia coli isolated from a swine cecum sample collected at a slaughter, in Portugal. Antimicrobial susceptibility phenotype of E. coli LV23529 showed resistance to colistin at a minimum inhibitory concentration of 4 mg/L. Whole genome of E. coli LV23529 was sequenced using a MiSeq system and the assembled contigs were analyzed for the presence of antibiotic resistance and plasmid replicon types using bioinformatics tools. We report a novel mcr-1 gene variant (mcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…Interestingly, almost all mcr-4 isolates belonged to the clonal group ST10-A (CH11-24) (García et al, 2018), which was shown to be highly present (more than 50%) within the mcr-1 diarrheagenic isolates of a second study (García-Meniño et al, 2018). Both studies reinforced other countries’ findings that the pig industry is an important reservoir of colistin-resistant E. coli , as well as being carriers of other additional risk genes such as bla ESBL genes (García et al, 2018; García-Meniño et al, 2018; Magistrali et al, 2018; Manageiro et al, 2019). Based on reported evidences (Beyrouthy et al, 2017; Gilrane et al, 2017), there is great concern about the in vivo acquisition of mcr- and bla ESBL -bearing plasmids by human E. coli isolates following treatment with colistin, or via animal transmission through direct contact or via food chain.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, almost all mcr-4 isolates belonged to the clonal group ST10-A (CH11-24) (García et al, 2018), which was shown to be highly present (more than 50%) within the mcr-1 diarrheagenic isolates of a second study (García-Meniño et al, 2018). Both studies reinforced other countries’ findings that the pig industry is an important reservoir of colistin-resistant E. coli , as well as being carriers of other additional risk genes such as bla ESBL genes (García et al, 2018; García-Meniño et al, 2018; Magistrali et al, 2018; Manageiro et al, 2019). Based on reported evidences (Beyrouthy et al, 2017; Gilrane et al, 2017), there is great concern about the in vivo acquisition of mcr- and bla ESBL -bearing plasmids by human E. coli isolates following treatment with colistin, or via animal transmission through direct contact or via food chain.…”
Section: Introductionsupporting
confidence: 75%
“…Since the mcr-1 plasmid gene was first described (Liu et al, 2016), it has been identified in members of the Enterobacteriaceae family encoded in different plasmid types, including IncI2, IncX4, IncHI1, IncHI2, IncFI, IncFII, IncP, IncK (Sun et al, 2018). Different authors corroborate that large conjugative plasmids of types IncHI2, IncX4 and IncI2 would be the maximum responsible for the dissemination of the mcr-1 gene among E. coli isolates from different sources and geographical locations (Doumith et al, 2016; Li et al, 2017; Manageiro et al, 2019). To date, other mcr genes (2–9) have been described (Carroll et al, 2019); among them, the mcr-4 and mcr-5 genes appear mostly encoded in small and non-conjugative ColE-like type plasmids (Sun et al, 2018).…”
Section: Resultsmentioning
confidence: 90%
“…Plasmid prediction using whole genome sequences identified several putative types of plasmids harbored by the eight strains (Figure 4). Among these putative types of plasmids, IncHI2A, IncFIB(K), IncFII, IncFI1, IncR, IncHI2, and IncFIA plasmids carrying bla NDM-1 have been reported [33,34,35,36,37], while IncX4, IncFIB(K), IncFII, IncFI1, IncY, IncHI2, IncX1, and IncFIA plasmids carrying mcr-1 have been reported [38,39,40,41,42]. Although more accurate and reliable technologies such as the third-generation sequencing technologies are necessary for determining the accurate type and sequence of the plasmids, bioinformatical analysis using whole genome sequences revealed that an IncFII-type plasmid homologous to pHNEC55 (GenBank accession: KT879914) likely carried the bla NDM-1 gene, and an IncX4-type plasmid homologous to pIBMC_mcr1 (GenBank accession: MF449287) likely carried the mcr-1 gene, as the backbones of both plasmids were found in the genomes of the eight strains (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 22 functional genetic variants of mcr-1 have been assigned [75][76][77][78][79][80][81][82], including mcr-1.1 [35], mcr-1.2 [83], mcr-1.3 [84], mcr-1.4 [85], mcr-1.5 [86], mcr-1.6 [87], mcr-1.7 [85], mcr-1.8 [43], mcr-1.9 [88], mcr-1.10 [75], mcr-1.11 [89], mcr-1.12 [43], mcr-1.13 [90], mcr-1.14 [71], and mcr-1.15 [91], while the other genetic variants from mcr-1.16 to mcr-1.22, were uploaded to NCBI GenBank (https://www.ncbi. nlm.nih.gov/nuccore/NG_065944.1).…”
Section: Plasmid-mediated Resistance To Polymyxinsmentioning
confidence: 99%